Neuropathic Pain in Syringomyelia: A Case Report and Comprehensive Review of Clinical Management - Rizaldy Taslim Pinzon; Bernadeta Amaya; Stefanus Erdana Putra (Lumina : Indonesian Journal of Neurology, 2026)
Introduction: Syringomyelia is an uncommon chronic spinal cord disorder characterized by the formation of a fluid-filled cavity (syrinx) within the neural parenchyma. This condition leads to progressive neurological impairment and severe neuropathic pain. This case report discusses the clinical presentation and comprehensive management of a patient with this condition. Case Presentation: A 39-year-old female presented with a two-year history of severe burning pain, sensory loss in a "cape-like" distribution, and progressive weakness of the hands. Magnetic Resonance Imaging (MRI) of the cervical and thoracic spine demonstrated a prominent, hyperintense cervicothoracic syrinx (C2–T2) secondary to adult Chiari malformation type 1 (CM1). Discussion: Initial gabapentin and amitriptyline yielded only partial pain control. Due to progressive lower motor neuron decline and refractory neuropathic pain, surgical intervention was indicated. Although foramen magnum decompression (FMD) remains the primary standard of care for restoring craniocervical CSF flow, a targeted syringo-subarachnoid shunting (SSS) procedure at the T1 level was used as a secondary rescue intervention to achieve rapid mechanical decompression of the massive, tense syrinx. Postoperatively, the patient demonstrated significant neurological improvement, with the Numeric Pain Rating Scale (NPRS) score decreasing from 7–8 to 3–4, alongside gradual motor recovery. Conclusions: Neuropathic pain in syringomyelia is complex and requires a multimodal, multidisciplinary approach. While FMD is the primary gold standard for Chiari I-associated syringomyelia, SSS represents a viable secondary option for rapid mechanical decompression in cases presenting with giant, highly symptomatic syrinxes and progressive motor decline, despite carrying higher long-term revision and complication risks. Keywords: Chiari Malformation, Chronic Pain, Neuropathic Pain, Syringomyelia, Syringo-Subarachnoid Shunt